PENGUASAAN KONSEP: BERPENGARUHKAN TERHADAP KEMAMPUAN MENGAJAR? - Wulandari, Tri Candra; Rahayu, Sri; Pranyata, Yuniar Ika Putri (Pi: Mathematics Education Journal, 2018)
The aims of this study is to determine the level of correlation between the ability of concept mathematics with the ability of teaching for mathematics students in mathematics education program. Referring to the purpose, this research is a correlational research using quantitative approach on 56 students of mathematics education who are taking courses Kajian Pengembangan Matematika Sekolah 3 (KPMS3). The data obtained using the test, namely the ability of concepts mathematics test and results of teaching practice. The results of data were analyzed using Pearson Product Moment to see correlation level, while hypothesis test of this research using Independent t-test with SPSS program. Results of data processing obtained that the level of correlation is 0.133 with significance 0.173. The result means that in this class, the ability of mathematics concept has a very low level of correlation, with meaning that the ability teaching math of students is not only influenced by the ability of mathematics concept. The result of processing data also supported by a significance level of 0.173, which can be concluded that there is no influence between the ability of mathematics concept with the ability of teaching mathematics on mathematics students. There is a need for further research related to the readiness of prospective teachers before teaching practice in schools.